The effect of co-morbid anxiety on remission from depression for people participating in a randomised controlled trial of the Friendship Bench intervention in Zimbabwe. (June 2020) - Abas, Melanie Amna; Weiss, Helen Anne; Simms, Victoria; Verhey, Ruth; Rusakaniko, Simbarashe; Araya, Ricardo; Chibanda, Dixon
Abstract: Background: There is a lack of data from low- and middle-income countries on whether anxiety independently predicts a more chronic course for depression. Methods: We undertook secondary data analysis of a cluster randomised controlled trial in Zimbabwe which had tested the effectiveness of the Friendship Bench intervention for common mental disorders compared to enhanced usual care. Inclusion for the current study was participants from the trial who had probable major depression at baseline, defined as scoring => 11 on the locally validated Patient Health Questionnaire (PHQ9). This emerged to be 354 of the original 573 (61.78%) of the original trial sample. Anxiety was measured using the locally validated cut-point on the Generalised Anxiety Disorder scale (GAD-7). Persistent depression was defined as scoring => 11 on the PHQ-9 at six-months follow-up. Analysis in Stata 15 used random-effects logistic regression to adjust for clustering by clinic. Outcomes: Of the 354 participants who were eligible for treatment, 329 (92·9%) completed 6-month follow-up assessment. 37% of the trial sample had persistent depression at 6-months follow-up; 59% in the control arm and 17% in the intervention arm. Co-morbid anxiety present at trial baseline was independently associated with persistent depression after adjusting for age, gender and baseline depression severity (adjusted OR = 2·83, 95% CI 1·32–6·07). There was no evidence of effect modification by trial arm. Baseline depression severity also predicted persistent depression. Interpretation Treatment for depression in low and middle-income countries (LMIC) should be directed towards those with greatest need. This includes people with co-morbid anxiety and greater depression severity at initial assessment who are less likely to remit at six months. Advice on coping with anxiety, psychological treatments which target common anxiety symptoms such as fear, avoidance, excessive worry and intrusive thoughts, and Selective Serotonin Reuptake Inhibitors (SSRIs) should be made more widely available in LMIC and offered to those with persistent mixed depression and anxiety.